2014
DOI: 10.4314/ijbcs.v8i3.22
|View full text |Cite
|
Sign up to set email alerts
|

Inventaire ethno-pharmacologique des plantes utilisées dans le traitement des pathologies parasitaires dans les élevages extensifs et semi-intensifs du Bénin

Abstract: . digitata, A. sativum, Anacardium occidentale, A. leiocarpa, B. ferruginea, C. papaya, C. ambrosioides, K. senegalensis, F. sur, M. inermis, N. canensis pour traiter les helminthiases. Les organes les plus utilisés sont les feuilles et les écorces. La majorité des remèdes sont préparés sous forme de décoction. Des tests sur l'efficacité de ces plantes permettront de mieux les valoriser dans la lutte contre les pathologies parasitaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
12
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 8 publications
8
12
0
5
Order By: Relevance
“…In addition the vernonioside antiparasitic activity against Eimeria is also possible, for, many antiparasitic effect of V. amigdalina have been reported. Antiprotozoan and anthelmintic properties (Abosi and Raseroka, 2003;Adiukwu et al, 2011;Ogni et al, 2014), anti-tumour properties (Izevbigie et al, 2004;Sweeney et al, 2005;Song et al, 2005;Opata and Izevbigie, 2006), hepato-protective activity (Ojiako and Nwanjo, 2006;Arhoghro et al, 2009) and anti-bacterial effect (Hamil et al, 2003;Bolou et al, 2011) have been demonstrated. It is also reported hat V. amygdalina provide anti-oxidant benefits (Erasto et al, 2007) and enhance the immune system through cytokines and chemokines regulation (Sweeney et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In addition the vernonioside antiparasitic activity against Eimeria is also possible, for, many antiparasitic effect of V. amigdalina have been reported. Antiprotozoan and anthelmintic properties (Abosi and Raseroka, 2003;Adiukwu et al, 2011;Ogni et al, 2014), anti-tumour properties (Izevbigie et al, 2004;Sweeney et al, 2005;Song et al, 2005;Opata and Izevbigie, 2006), hepato-protective activity (Ojiako and Nwanjo, 2006;Arhoghro et al, 2009) and anti-bacterial effect (Hamil et al, 2003;Bolou et al, 2011) have been demonstrated. It is also reported hat V. amygdalina provide anti-oxidant benefits (Erasto et al, 2007) and enhance the immune system through cytokines and chemokines regulation (Sweeney et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Dans la majorité des élevages parcourus, les éleveurs sont majoritairement d'ethnie peulh. Ce résultat corrobore ceux obtenus par , Ogni et al (2014) et Kpodékon et al (2015a) qui ont également mené des enquêtes ethno-pharmacologiques sur l'ensemble du territoire béninois.…”
Section: Discussionunclassified
“…Les paramètres impactés les plus fréquemment cités sont, par ordre d'importance : la perte de la fertilité des sols, le travail difficile de ces types de sols et le faible enracinement des cultures pouvant entrainer leur chute en cas de vent violent. Les indicateurs végétaux sont caractérisés de bio-indicateurs par des études antérieures (Chotte et al, 2001;IlboudoTapsoba et al, 2011;Ogni et al, 2014) (Temgoua et al, 2002). On peut y ajouter également des zones de pavage de cailloux et de pierres laissés en surface, une fois que les particules les plus fines du sol sont emportées par le ruissellement (Kabré, 2009).…”
Section: Perception Locale De La Dynamique Des Surfaces Cuirasséesunclassified